2008
DOI: 10.1002/ijc.23614
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lariciresinol attenuates mammary tumor growth and reduces blood vessel density in human MCF‐7 breast cancer xenografts and carcinogen‐induced mammary tumors in rats

Abstract: Lariciresinol is a dietary lignan that accounts for a significant portion of the total phytoestrogen intake from Western foods. Recent epidemiological studies suggest that high dietary intake of lignans and lariciresinol is associated with reduced breast cancer risk. However, no causal relationship between lariciresinol intake and breast cancer development has been established. In this study, we investigated for the first time the effects and possible mechanisms of action of lariciresinol on hormone responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…As it is well documented that plant lignans also have potent antitumorigenic activity with minimal side effects (Thompson et al, 1996;Bylund et al, 2005;Saarinen et al, 2008), we tested whether this activity could involve sensitization to death receptor signaling. A number of closely related lignans ( Figure 1a) were tested in a non-toxic concentration for their capacity to sensitize LNCaP prostate cancer cells to TRAIL receptor-mediated apoptosis in the prescence or absence of androgen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is well documented that plant lignans also have potent antitumorigenic activity with minimal side effects (Thompson et al, 1996;Bylund et al, 2005;Saarinen et al, 2008), we tested whether this activity could involve sensitization to death receptor signaling. A number of closely related lignans ( Figure 1a) were tested in a non-toxic concentration for their capacity to sensitize LNCaP prostate cancer cells to TRAIL receptor-mediated apoptosis in the prescence or absence of androgen.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that lignans inhibit proliferation and are cytotoxic to prostate cancer cell lines (Lin et al, 2001, Chen et al, 2007. Moreover, lignans can prevent tumor growth and induce apoptosis in vivo in prostate cancer xenografts or chemically induced mammary tumors (Bylund et al, 2005;Saarinen et al, 2008;Thompson et al, 1996) and can also reduce experimental metastasis (Li et al, 1999). Plant-derived lignans, such as matairesinol (MAT), are metabolized by mammalian gut microflora resulting in enterolactone (ENL) or enterodiol (Axelson et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…exhibited strong cytotoxicity against a variety of cancer cell lines in vitro, which correlated positively with the number of O-methyl groups in the molecule [233]. Experimental data have shown that some plant lignans were effective against tumor growth and tumor-associated angiogenesis exclusively in hormone responsive mammary cancer [234,235] and not in hormone irresponsive intestinal tumors [236]. Moreover, the number and size of intestinal tumors increased significantly in mice fed with matairesinol [236].…”
Section: Interaction With Estrogen Receptorsmentioning
confidence: 99%
“…(Holmbom et al, 2003). Best known among those from the genus Abiesis secoisolariciresinol, a potent natural antioxidant found in balsam knots alongside lariciresinol which has proven bioactivity against breast cancer (Saarinen et al, 2008). Knot extracts contain juvabione and sesquiterpenoïd acids as well (Figure 1).…”
Section: Current Knowledge On Abies Extractives and Their Biological mentioning
confidence: 99%